The Instruments Used In Measuring Internet Addiction: A Review - Kudus, Norliah; Sidek, Safiah; Abu Hassan, Mahadi; Mohamed, Shahrulanuar; Aripin, Muhamad Afzamiman (Academic Publications, 2018)
The growing attention of internet addiction problem has urged the researchers worldwide to develop an instrument to measure internet addiction level among worldwide population. Many of them have develop and adapt the diagnostic and test scale to identify the level of internet addiction among population. Thus, this study are going to conduct comparison analysis of the instruments used based on different platforms, the number of study used and different aspects included to other study .The assessment used in 28 studies will be discussed based on three type of analysis. Based on this review, IAT instrument was found to be the higher assessment used by the number of studies in order to evaluate internet addiction level which comprise of three dimensions. Most of these studies are mainly drawn from the field of psychology. This review will provide deep understanding on instrument construct to future study in developing new instrument based on internet addiction phenomenon